Secondhand smoke exposure in adulthood and risk of lung cancer among never smokers: a pooled analysis of two large studies. - Brennan, P; Buffler, P; Reynolds, P; Wu, A; Wichmann, H; Agudo, A; Pershagen, G; Jöckel, K; Benhamou, S; Greenberg, R; Merletti, F; Winck, C; et al. (2004)
The interpretation of the evidence linking exposure to secondhand smoke with lung cancer is constrained by the imprecision of risk estimates. The objective of the study was to obtain precise and valid estimates of the risk of lung cancer in never smokers following exposure to secondhand smoke, including adjustment for potential confounders and exposure misclassification. Pooled analysis of data from 2 previously reported large case-control studies was used. Subjects included 1263 never smoking lung cancer patients and 2740 population and hospital controls recruited during 1985-1994 from 5 metropolitan areas in the United States, 11 areas in Germany, Italy, Sweden, United Kingdom, France, Spain and Portugal. Odds ratios (ORs) of lung cancer were calculated for ever exposure and duration of exposure to secondhand smoke from spouse, workplace and social sources. The OR for ever exposure to spousal smoking was 1.18 (95% CI = 1.01-1.37) and for long-term exposure was 1.23 (95% CI = 1.01-1.51). After exclusion of proxy interviews, the OR for ever exposure from the workplace was 1.16 (95% CI = 0.99-1.36) and for long-term exposure was 1.27 (95% CI = 1.03-1.57). Similar results were obtained for exposure from social settings and for exposure from combined sources. A dose-response relationship was present with increasing duration of exposure to secondhand smoke for all 3 sources, with an OR of 1.32 (95% CI = 1.10-1.79) for the long-term exposure from all sources. There was no evidence of confounding by employment in high-risk occupations, education or low vegetable intake. Sensitivity analysis for the effects of misclassification (both positive and negative) indicated that the observed risks are likely to underestimate the true risk. Clear dose-response relationships consistent with a causal association were observed between exposure to secondhand smoke from spousal, workplace and social sources and the development of lung cancer among never smokers.